The Extended Theory of Planned Behavior: Understanding Intention to Use Public Transportation Through Culture Based Public Transportation : In A Review - Prima Widayanto (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2023)
From the results of the elaboration of twelve articles and the existence of problems and the purpose of this article in the form of a review of articles related to the SDGs model  by adding culture-based public transportation variables  using the SOR model approach to the SDGs model. The formation of culture-based public transportation variables  as a research update is based on the background of multi-cultural public transportation users  in Indonesia, namely users with different backgrounds, needs, and preferences.